Analisis Fiqh Terhadap Kartu Kredit Syariah - Ahmad Fatoni (MUAMALATUNA, 2022)
Along with the development of modern finance, the need for safe and efficient means of payment has become a necessity. Credit cards are the solution to answering these needs. The scholars agreed that credit cards are forbidden in Islam because of the interest in the mechanism, so an agreement emerged to create a credit card with a mechanism that is under sharia principles. However, differences of opinion among scholars arose mainly regarding the underlying contracts and the requirements that must be met on Islamic credit cards. This study aims to find out various fiqh analyses of scholars regarding the ability of Sharia credit cards. This type of research is qualitative with the library research method. The results showed that in general, scholars allow sharia credit cards. However, there are differences regarding the taking of fees on the kafalah contract, profit from administrative costs, and ta'widh on late fees.